2017
DOI: 10.20961/jdc.v1i2.17622
|View full text |Cite
|
Sign up to set email alerts
|

Pendidikan Karakter Peduli Lingkungan Dan Implementasinya

Abstract: Pola pendidikan sekolah bergerak dan berkembang sesuai dengan perkembangan ilmu pengetahuan teknologi yang tidak hanya mengajarkan aspek kognitif (pengetahuan)  saja melainkan juga aspek afektif (sikap) dan aspek psikomotor (perilaku/kebiasaan). Berkaitan dengan sikap afektif, pemerintah telah menetapkan pendidikan karakter. Salah satu karakter yang dikembangkan adalah peduli lingkungan. Kajian ini difokuskan pada (1) konsep pendidikan karakter peduli lingkungan dan (2) implementasi pendidikan karakter peduli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
83

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 0 publications
0
47
0
83
Order By: Relevance
“…If you violate, you will get a penalty. If the most obedient get an award [14] and [15]. Educational methods used are reward and punishment, orders and prohibitions, praise, good examples, and habituation.…”
Section: Discussionmentioning
confidence: 99%
“…If you violate, you will get a penalty. If the most obedient get an award [14] and [15]. Educational methods used are reward and punishment, orders and prohibitions, praise, good examples, and habituation.…”
Section: Discussionmentioning
confidence: 99%
“…Video pembelajaran ini dapat membangun karakter siswa untuk peduli terhadap lingkungan. Karakter peduli lingkungan ialah salah satu karakter yang wajib diimplementasikan dan ditanamkan oleh semua jenjang pendidikan kepada peserta didiknya (Purwanti, 2017).…”
Section: Pendahuluanunclassified
“…Setiap orang harus memiliki sikap peduli terhadap lingkungan hidup dan mempunyai ide dan gagasan untuk mencegah terjadinya kerusakan lingkungan. Pendidikan karakter terhadap peduli lingkungan harus ditanamkan sejak dini, agar terbentuknya rasa tanggung jawab terhadap generasi selanjutnya (Purwanti, 2017). Pendidikan karakter terhadap lingkungan memiliki peran penting terhadap majunya kualitas kehidupan bangsa.…”
Section: Pendahuluanunclassified
“…Fathurrohman (2016) suggested that character is formed through education, education as an effort to inherit community values and transform these values to face the era of globalization, so the quality of education needs to be improved. According to Hendriana and Jacobus (2016) Purwanti (2017) asserted that the character of environmental care can be understood as one of the character values of a number of Indonesian national characteristics which can be seen from the attitude and individual to maintain and improve the environment properly for the benefit of humanity itself. So it can be concluded that the character of environmental care is an individual character that relates to values in society, these characters appear in the form of human actions in maintaining and managing the environment effectively and efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…(2) preventing destructive behavior of the environment, (3) increasing awareness of students about environmental care, (4) training students to be responsible utilizing the environment, and (5) being a savior of the environment that can be imitated by people around him (Purwanti, 2017). Al-Anwari (2014) asserted that the character of students' environmental care must be formed in the school environment through environmental care activities such as adiwiyata activities.…”
Section: Introductionmentioning
confidence: 99%